The role of wood extractives in structural hardwood bonding and their influence on different adhesive systems. (June 2019) - Bockel, S.; Mayer, I.; Konnerth, J.; Harling, S.; Niemz, P.; Swaboda, C.; Beyer, M.; Bieri, N.; Weiland, G.; Pichelin, F.
Abstract: Bonding of hardwood for structural applications is a complex process. Various factors influence the bond performance and the interface area is considered the most crucial part. The chemical composition of the interface, e.g. wood extractives, is expected to influence the bonding of hardwoods. The subject of this study was to determine the influence of seven model substances that represent common wood extractives on different adhesive systems namely one-component polyurethane, two-component polyurethane, melamine urea formaldehyde and phenol resorcinol formaldehyde. The influence of the model substances on the cross-linking behavior of the adhesives was determined by attenuated total reflection Fourier transform infrared spectroscopy (ATR-FTIR) and on the rheological properties in terms of gel point and storage modulus. In addition, model substances characteristic for selected wood extractives were applied to the surface of European beech wood [ Fagus sylvatica L.] before bonding and consequently tested in tensile shear mode according to EN 302-1. The ATR-FTIR spectra showed an influence of some substances on the crosslinking for all adhesive systems. Further, the curing process was mostly accelerated for phenol resorcinol formaldehyde, while melamine urea formaldehyde and polyurethane showed a less negative change in rheological behavior. The mechanical strength of beech wood bonds at room climate indicated only minor influence of model substances, but samples tested in wet conditions demonstrated a significant effect on some adhesive systems. It was concluded, that polyurethane adhesives degrade by acid substances and melamine urea formaldehyde by starch and gallic acid. Phenol resorcinol formaldehyde system was influenced negatively by starch and acids.